Inter-center variability in neonatal outcomes of preterm infants: A longitudinal evaluation of 298 neonatal units in 11 countries. Issue 1 (February 2021) - Lui, Kei; Vento, Maximo; Modi, Neena; Kusuda, Satoshi; Lehtonen, Liisa; Håkansson, Stellan; Rusconi, Franca; Bassler, Dirk; Reichman, Brian; Yang, Jie; Shah, Prakesh S.; et al.
Abstract: Collaboration and cooperation of clinicians and neonatal units at regional, national, and international levels are key features of many networks or systems that aim to improve neonatal outcomes. Network performance is typically assessed by comparing individual, unit-level outcomes. In this paper, we provide insight into another dimension, i.e., inter-center outcome variation in 10 national/regional neonatal collaborations from 11 high-income countries. We illustrate the use of coefficients of variation for evaluation of mortality and a composite outcome of mortality, severe neurological injury, treated retinopathy of prematurity, and bronchopulmonary dysplasia, as a measure of inter-center variation. These inter-center variation estimates could help to identify areas of opportunities and challenges for each country/region; they also provide "macro"-level evaluations that can be useful for clinicians, administrators, managers and policy makers.